Exploring therapeutic paradigm focusing on genes, proteins, and pathways to combat leprosy and tuberculosis: A network medicine and drug repurposing approach - Mohd Imran; Ahmed S. Alshrari; Mariah N. Hafiz; Mohammed M. Jawad; Abida Khan; Fadiyah Jadid Alanazi; Syed Mohammed Basheeruddin Asdaq (Journal of Infection and Public Health)
Background: Leprosy and tuberculosis caused by Mycobacterium leprae and Mycobacterium tuberculosis, respectively, are chronic infections with significant public health implications. While leprosy affects the skin and peripheral nerves and tuberculosis primarily targets the lungs, both diseases involve systemic immune responses. This study integrates transcriptomic analysis cheminformatics and molecular dynamics simulations to identify molecular mechanisms and potential therapeutic targets. Methods: Transcriptomic datasets were analyzed to identify dysregulated genes and pathways. Pathway enrichment tissue-specific and bulk RNA-seq expression analyses provided biological context. System biology networks revealed regulatory hub genes and molecular docking studies evaluated CHEMBL compounds as potential therapeutics. Molecular dynamics (MD) simulations assessed the stability of top ligand-protein complexes through RMSD RMSF and MM-GBSA free energy calculations. Results: Gene expression analysis identified 13 core dysregulated genes, including HSP90AA1 MAPK8IP3 and ZMPSTE24. Tissue-specific expression localized pivotal genes to lung tissues and immune cells with HSP90AA1 highly expressed in alveolar macrophages and epithelial cells. HSP90AA1 gene emerged as a central hub gene with 96 interactions involved in stress response pathways. Docking studies identified CHEMBL3653862 and CHEMBL3653884 with strong binding affinities (-10.16 to −12.69 kcal/mol) interacting with Asp93 and Tyr139. MD simulations confirmed binding stability with RMSD fluctuations within 2.1–3.5 Å and MM-GBSA energy values supporting ligand-protein stability. Conclusion: This study identifies HSP90AA1 as a potential drug target in leprosy and tuberculosis. Findings support host-directed therapy approaches and highlight the importance of computational modeling in accelerating drug discovery. The study provides a foundation for future experimental validation, including in vitro and in vivo testing to advance drug repurposing strategies for these chronic infections.